Chromatin complex dependencies reveal targeting opportunities in leukemia - Fadi J. Najm; Peter DeWeirdt; Molly M. Moore; Samantha M. Bevill; Chadi A. El Farran; Kevin A. Macias; Mudra Hegde; Amanda L. Waterbury; Brian B. Liau; Peter van Galen; John G. Doench; Bradley E. Bernstein (Nature Communications, 2023)
Epigenetic regulators are potential therapeutic drug targets in leukemia. Here, the authors perform combinatorial CRISPR knockouts to test gene-gene pairings in leukemia cells to discover compensatory non-lethal or synergistic lethal combinations with therapeutic potential.